Transmission Line Congestion Management for Large-scale Renewable Energy Access to Power Grid with DSM. Issue 6 (April 2019) - Liu, Zhengfu; Lu, Qifu; Kong, Xiangyu; Wang, Hongxing; Sheng, Chao; Quan, Suping; Wang, Yuting
Abstract: With the depletion of fossil energy, governments are paying more and more attention to wind power and photovoltaic power generation. The power price of demand side management (DSM) may be of volatility and spike because of transmission congestions. a congestion management strategy for large-scale renewable energy access to power grid with demand side management is proposed in the paper. This paper puts forward the goal of maximizing social benefits, analyses the congestion management model under the premise of considering demand elasticity, and puts forward two-level solutions. studies on the IEEE 30-bus system are presented to verify the validity of the method.